(untitled) - Shou, Corey (Boston, 2007)
Information Assurance for the Enterprise provides readers an overarching model for information assurance for businesses, government agencies, and other enterprises needing to establish a comprehensive plan. All the components of security and how they relate are featured, and readers will also be shown how an effective security policy can be developed...
Keywords: Computer security,Data protection,An toàn Máy tính,Bảo vệ dữ liệu